2012
DOI: 10.17816/kmj2102
|View full text |Cite
|
Sign up to set email alerts
|

Gender motivational traits of the disabled with lower limbs structural and functional deficiencies

Abstract: Aim. To define the motivational and gender differences in patients with limb loss. Methods. 318 patients [male - 267 (83.3%), female - 51 (16.7%)] with lower limbs structural and functional deficiencies admitted for prosthetics surgery to prosthetic and orthopedics center «Reabilitaciya invalidov», Kazan, Russia, from 2008 to 2010 were included in the study. Empiric data on motivational features were gained using questionnaires and test examinations of 191 patients aged form 18 to 66 years. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Together with schools, Tatar women were also visiting libraries, and became more and more included in charitable activities (see Biktimirova, 2011). From 1913 onward, the journal for women, Suyum-bike , started to be published in Kazan.…”
Section: Muslim Subjects Of the Russian Empire And New Ideas About Womentioning
confidence: 99%
See 3 more Smart Citations
“…Together with schools, Tatar women were also visiting libraries, and became more and more included in charitable activities (see Biktimirova, 2011). From 1913 onward, the journal for women, Suyum-bike , started to be published in Kazan.…”
Section: Muslim Subjects Of the Russian Empire And New Ideas About Womentioning
confidence: 99%
“…The biggest part of the scholarly knowledge about the Volga-Ural region analyzes Russian imperial politics and the development of modernization ideas in the region (see Ro’i, 2004; Tuna, 2015). The modernizers’ ( jadidist ) educational reforms and their thinking about progress of the nation and gender 1 became the focus of several important publications produced in Tatarstan (Biktimirova, 2011; Gimazova, 2004; Makhmutova, 2003, 2006; see also Rorlich, 2004). These works showed that at the beginning of the 20th century, the Tatar society experienced important changes with respect to views on a woman’s education and her role in the progress of the nation.…”
mentioning
confidence: 99%
See 2 more Smart Citations